Should the unemployed care for the elderly? The effect of subsidized occupational and further training in elderly care - Christine Martina Dauth; Julia Lang (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
Demographic change implies an increasing demand for elderly care and a lower labor force potential at the same time. Training unemployed workers in care occupations might mitigate this problem. This study analyzes the effectiveness of subsidized training in elderly care professions for the unemployed in Germany over 12 years. We find that subsidized further training and retraining in elderly care improves the employment chances of unemployed workers substantially in the long term. Moreover, a high share of these re-employed workers remain in the care sector. A high percentage of parttime work and conditional wage gains for only certain retraining participants indicate shortcomings in the quality of employment. However, subsidized training seems to be an adequate measure to re-employ unemployed workers in the elderly care sector and to narrow the gap between demand and supply in elderly care. – – Der demografische Wandel wirkt sich in doppelter Weise auf den Bedarf an Pflegepersonal aus. Während die Zahl der pflegebedürftigen Personen immer weiter ansteigt, sinkt das Erwerbspersonenpotenzial. Eine Möglichkeit, einem Fachkräftemangel in der Altenpflege entgegenzuwirken, ist die Qualifizierung Arbeitsloser in diesem Berufsfeld. In dieser Studie untersuchen wir die Effekte geförderter Weiterbildung in der Altenpflege für Arbeitslose in Deutschland über einen Zeitraum von 12 Jahren. Unsere Ergebnisse zeigen, dass geförderte Weiterbildung in der Altenpflege die Beschäftigungschancen von Arbeitslosen langfristig deutlich verbessert. Zugleich verbleibt ein hoher konstanter Anteil dieser wiederbeschäftigten Arbeitslosen langfristig im Pflegebereich. Auf ein Defizit bei der Arbeitsqualität deuten jedoch ein hoher Teilzeitanteil und nur partielle positive Lohneffekte für bestimmte Umschulungsteilnehmer hin. Generell scheinen Weiterbildungsmaßnahmen in der Altenpflege aber ein geeignetes Mittel um Arbeitslose langfristig in der Altenpflege zu beschäftigen, was einem Fachkräfteengpass in diesem Bereich entgegenwirken könnte.
Keywords: I11; J24; J68; 330; Training; elderly care; program evaluation; dynamic treatment effects; active labor market policy